2022
DOI: 10.18261/uniped.45.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Changing practices of Suitability Assessment in a Norwegian Education Dental Programme

Abstract: A profound responsibility of higher education is to educate and certify adequately candidates for professional work. However, there are signs indicating that many Norwegian professional programmes fail in this responsibility. In this article, we present and analyse a process of change in a five-year dental education programme at a Norwegian university that had the aim of developing more reliable certification practices through improving their suitability assessment practices. Whatever motivates a need for chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…A case study revealed how to implement a template to support students in becoming professionally suitable (Solbrekke and Moystad, 2022). Educators in practicum and at campus had close collaboration and gradually changed their assessment practices by using systematic evaluation of the students.…”
Section: Suitability Assessments In a Norwegian Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…A case study revealed how to implement a template to support students in becoming professionally suitable (Solbrekke and Moystad, 2022). Educators in practicum and at campus had close collaboration and gradually changed their assessment practices by using systematic evaluation of the students.…”
Section: Suitability Assessments In a Norwegian Contextmentioning
confidence: 99%
“…The purpose of mentoring in teacher education is to facilitate the PTs' learning and development thus mentors play a significant role in shaping the PT's professional identity (Hvalby and Thortveit, 2022). Developing suitability involves the ability or willingness to change behavior and attitude related to the profession (Solbrekke and Moystad, 2022), and an example is to obtain self-insight related to future professional role. This process is part of professional development and through mentoring the PTs practice reflecting and thinking critically when they analyze their actions (Carroll, 2010;Rankine, 2018).…”
Section: Suitability Assessments In a Norwegian Contextmentioning
confidence: 99%
See 3 more Smart Citations